Nature Meets Technology: A Case Study of Gambier Leaf and N719 Hybrid Sensitizer in DSSCs Application - Galih Saputri, Diani; Hirsi, Abdinasir; Abd Ahmed, Noor Kamalia; Shazleen, Ahmad Ramli; Nurhaziqah, A.M.S. Nurhaziqah; Faridah, A.B. Faridah; Supriyanto, A.; Ahmad, M.K.; Ribuan, M. N.; Rasman, N.H.; Ahmad, M.Y. (International Journal of Integrated Engineering, 2025)
Dye-sensitized solar cells (DSSCs) offer a cost-effective and eco-friendly renewable energy solution, with dye as sensitizers playing a crucial role in their performance. While synthetic dyes are commonly used, they are toxic and expensive, making natural dyes such as gambier a sustainable and environmentally friendly alternative. This study explores the role of dye in the performance of DSSC based-TiO2 as semiconductor, with a highly optimized surface, the dye is expected to absorb effectively, facilitating electron excitation. Morphological analysis confirmed that combining these materials enhances surface area and improves light scattering, boosting DSSC performance. To reduce synthetic dye usage and optimize the potential of natural gambier dye, a hybrid approach with the synthetic dye N719 was employed. Photovoltaic measurements revealed that this hybrid technique successfully optimized the natural dye’s potential, achieving an efficiency of 2.764%. These findings demonstrate that natural dye can be effectively utilized, offering a sustainable and non-toxic alternative for DSSC applications.